1999
DOI: 10.1007/s004200050381
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations at the T-cell antigen receptor in antineoplastic drug-exposed populations: comparison with sister chromatid exchange frequency

Abstract: Our data suggest that SCE frequency and HFC percentage are not reliable indicators of exposure to possible mutagenic/carcinogenic effects of antineoplastic drugs; on the contrary, our observations indicate that anticancer therapy induces somatic mutations at the TCR locus and suggest an association between exposure to cytotoxic agents and the increase in somatic mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…These ®ndings may be explained by the unspeci®c nature of these markers and the multitude of factors (e.g., individual susceptibility, variability in DNA repair, working conditions, lifestyle, study design, dosimetry procedures) that could have undesired in¯uences on the outcome of human biomonitoring studies. The lack of signi®cant dierences in SCE between exposed probands and controls observed in our study is in good accordance with recently published data (Lanza et al 1999, Kasuba et al 1999, and may be related to the use of protective equipment at work that is expected to determine the genotoxic impact of occupational exposure to anticancer drugs. For instance, Kevekordes et al (1998) found signi®cant increases of SCEs and MN frequencies in ten nurses who were considered to be exposed to high amounts of antineoplastic agents, after malfunction of a safety hood.…”
Section: Discussionsupporting
confidence: 93%
“…These ®ndings may be explained by the unspeci®c nature of these markers and the multitude of factors (e.g., individual susceptibility, variability in DNA repair, working conditions, lifestyle, study design, dosimetry procedures) that could have undesired in¯uences on the outcome of human biomonitoring studies. The lack of signi®cant dierences in SCE between exposed probands and controls observed in our study is in good accordance with recently published data (Lanza et al 1999, Kasuba et al 1999, and may be related to the use of protective equipment at work that is expected to determine the genotoxic impact of occupational exposure to anticancer drugs. For instance, Kevekordes et al (1998) found signi®cant increases of SCEs and MN frequencies in ten nurses who were considered to be exposed to high amounts of antineoplastic agents, after malfunction of a safety hood.…”
Section: Discussionsupporting
confidence: 93%
“…The suppressive action of protease inhibitors on tumor cells in vitro [45] and tumors in vivo [34][35][36][37][38][39][40][41][42] has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three types, Kunitz inhibitors are the largest with a molecular means of about 20 kDa while squash inhibitors are the smallest with a molecular mass of approximately 3 kDa. These protease inhibitors are known for their antitumor and anti-pest activities [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Protease inhibitors are also produced by animals [46].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found an association between increase in sisterchromatid exchanges (SCE) [Sardas et al, 1991;GoloniBertollo et al, 1992], micronuclei (MN) [Yager et al, 1988;Anwar et al, 1994;Machado-Santelli et al, 1994], chromosome aberrations (CA) [Milkovic-Kraus and Horvat, 1991;Goloni-Bertollo et al, 1992;Grummt et al, 1993;Anwar et al, 1994], premature centromere division [Major et al, 1999], and DNA damage [Ü ndeger et al, 1999] and chronic exposure to these drugs. On the other hand, others have not observed any cytogenetic effect related to exposure [Benhamou et al, 1988;Cooke et al, 1991;Roth et al, 1994;Brumen et al, 1995;Ensslin et al, 1997;Lanza et al, 1999;Hessel et al, 2001]. Safety recommendations for handling these drugs have been issued by authorities in several countries, but there is still a great concern about the possible adverse effects of occupational exposure.…”
Section: Introductionmentioning
confidence: 95%